Penerapan Elastic Stack sebagai Platform Visualisasi dan Analisis Trafik pada Jaringan Riset dan Edukasi - Muhammad Rafi Fauzan Fathin; Achmad Basuki; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Network monitoring is an essential part of a computer network, where monitoring functions monitor the status and activity of network devices. To effectively ensure the security and quality of the network, monitoring is needed to provide detailed network traffic information. However, in general, many network monitoring uses the Simple Network Management Protocol (SNMP) because it has become the industry standard in network monitoring. In the case of network monitoring with wide coverage, such as IDREN, using the SNMP protocol is considered by the manager to be less effective, because it only provides minimal data visibility and measures bandwidth usage. This final project proposes a monitoring platform or visualization and analysis of research and education network traffic using Elastic Stack because it can display detailed network traffic data in various appearance. Implementation of network traffic visualization and analysis platform in this research requires two main components: a router with the Netflow protocol and an Elastic Stack Server. Routers that already have the Netflow protocol are used as gateways for incoming and outgoing network traffic, collecting metadata on the IP network and sending it to the Netflow Collector. Meanwhile, Elastic Stack is used instead of Netflow Collector using the Logstash system, metadata storage and analysis using the Elasticsearch system, and visualization with the help of Kibana. The test results show that the visualization and analysis platform implemented runs according to its function in providing detailed network traffic data in various visualization displays. Based on the test, the performance of Elastic Stack as a network traffic visualization and analysis platform can manage data from 97 B to 110 MB per 30 minutes and display that data in various visualizations and analyses in real-time.